EFFECT OF LAND-BASED POLLUTION ON CENTRAL JAVA CORAL REEFS - Evan N. Edinger; Michael J. Risk (JOURNAL OF COASTAL DEVELOPMENT, 2000)
Land-based pollution has severely damaged nearshore corals reefs in the Jepara area, Central Java. Effect described here include reduced coral cover and diversity, high coral mortality, reduced reef habitat complexity, and increased bioerosion intensity, compared to reference reefs in the Karimunjawa Islands National Marine Park, Central Java. Furthermore, the polluted reefs have negative net carbonate production indicating net reef erosion. Reef health parametres based on coral cover and diversity and on net carbonate production are inversely correlated with chlorophyll A concentration, suggesting eutrophication of coastal waters as a key agent of reef degradation. Untreated sewage dumping, agricultural runoff, and aquacultural effluent all contribute to nearshore eutrophication in Central Java, but it is not possible from this study to determine which of these types of land-based pollution is most responsible for degradation of Central Java reefs. Efforts to restore the condition of degraded reefs must begin with controlling sources of land-based pollution.